Investigate the factors affecting safety culture in the Malaysian mining industry - Siti Noraishah, Ismail; Azizan, Ramli (Elsevier, 2023)
Nowadays, safety culture is critical in preventing near-misses, accidents, and disasters. It has three dimensions: psychological, situational, and behavioural. To the best of the author’s knowledge, lack of research has been done on psychological and behaviour safety culture in the Malaysian mining industry. The objective of the study is to investigate the factors affecting psychological and behaviour safety culture in the Malaysian mining in- dustry. A two-round online Delphi method was performed among mining experts. The Delphi Experts (n = 21) with extensive experience in mining operations volunteered in this study. The Delphi I (open ended interview) and Delphi II (questionnaire survey) were completed by 100% (n = 21/21) and 87.5% (n = 18/21) of the experts, respectively. Thematic analysis was used to analyse the Delphi I and generate five and nine themes for psychological, situational and behaviour factors. For psychological safety culture, the Delphi II resulted median, IQD and percentage distribution analysis with 83.3%, 83.3% with the IQD cut-off (IQD ≤1) and 64.81% respectively. For situational, safety culture, the consensus was achieved with median, IQD and total percentage distribution analysis with 94.4%, 61.1% and 73.15%, respectively For behavioural safety culture, the consensus was achieved with median, IQD and total percentage distribution analysis with 94.4%, 66.7% and 73.6%, respectively. To conclude, the Delphi analysis revealed that experts agreed and consensuses were achieved on five, ten and nine factors that have major impacts on psychological, situational and behavioural safety culture in the Malaysian mining industry.